2015
DOI: 10.2147/opth.s73855
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser-assisted implantation of complete versus incomplete rings for keratoconus treatment

Abstract: PurposeTo compare complete versus incomplete ring implantation for keratoconus correction.MethodsWe investigated 25 eyes of keratoconic patients, of which 15 had femtosecond-assisted MyoRing corneal implantation (Group 1) and 10 had femtosecond-assisted Keraring segments (Group 2). Uncorrected distance visual acuity (UCVA), best corrected distance visual acuity (BCVA), mean K (Km), sphere, topographic cylinder, and corneal asphericity value (Q-value) were measured in all eyes preoperatively and at 4 weeks post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
(30 reference statements)
3
13
0
1
Order By: Relevance
“…Other studies evaluating the outcomes of KeraRing implantation but in keratoconus patients have also shown a positive change of anterior corneal asphericity. 23,24 This change to a less prolate shape indicates the ability of the ring segments to reduce the corneal protrusion generated by the ectasia. Likewise, in agreement with previous studies conducted on keratoconus patients, [25][26][27] a significant change in the steepest posterior corneal curvature was induced with the implantation of the ICRS.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies evaluating the outcomes of KeraRing implantation but in keratoconus patients have also shown a positive change of anterior corneal asphericity. 23,24 This change to a less prolate shape indicates the ability of the ring segments to reduce the corneal protrusion generated by the ectasia. Likewise, in agreement with previous studies conducted on keratoconus patients, [25][26][27] a significant change in the steepest posterior corneal curvature was induced with the implantation of the ICRS.…”
Section: Discussionmentioning
confidence: 99%
“…Mean decreased keratometry ratio in MyoRing to KeraRing groups reported by Al-Tuwairqi et al was 1.43 D (6.51/4.55) and the value reported by Hosny et al was 1.95 D, while in the present study this ratio was 3.11 and 2.43 D for the mean and maximum (Kmax) front surface keratometry, respectively. 25,26 There are studies, however, which reported no significant changes in mean and maximum keratometry readings between ICRS and CICR. 27 However, they mentioned more effect of MyoRing and 320-degree ring compared to two segments rings.…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Hosny et al, the corneal asphericity was evaluated only in a MyoRing with a diameter of 6 mm. [29] The mean change in the corneal asphericity was 0.43 ± 2.6 after the MyoRing implantation. The less favorable outcome of this study compared to the present study could be due to the difference in the duration of follow-up after the surgery.…”
Section: Discussionmentioning
confidence: 99%